PENGGUNAAN KEIGO PADA SITUS BELANJA DARING "AMAZON" DAN "RAKUTEN" - Amalia Septyani; Gita Aulia; Vera Yulianti (Jurnal SORA, 2018)
Keigo or Japanese language honorific expression is often used in the daily life of Japanese society, for instance in an online retail transaction between buyer and service provider. Yet, the rapid development of information technology has encouraged the changing of the transaction, from a conventional retail transaction which the buyer and the seller face to face directly, into a virtual world which known as an online network. These kinds of online retail transaction websites also appear in Japan, e.g. Amazon, Rakuten, and Jshoppers. This study focuses on the analysis of using honorifics or Keigo varieties in online retail transaction sites by comparing the websites between Amazon Japan and Rakuten Japan websites. The data is analyzed descriptively with the content analysis method. The result shows that the Japanese Rakuten online shopping website consistently uses Keigo on the instructions of each stage of the transaction. On the contrary, Amazon Japan online shopping website, the home base is in the United States, uses Teineigo instead of Keigo.